The Judgment Books: A Story - Benson, E. F. (Edward Frederic), 1867-1940; Hatherell, William, 1855-1928 (Salt Lake City, UT : Project Gutenberg, 2014)
"The Judgment Books: A Story" by E. F. Benson is a novel written in the late 19th century. The narrative revolves around Frank Trevor, an artist, as he grapples with themes of personal identity and artistic expression, particularly in relation to his decision to paint a portrait of himself. The story explores the psychological complexities associated with creating art, as well as the tension between Frank's artistic aspirations and his fears of losing himself and his connection with his wife, Margery. The opening of the novel introduces a serene Cornish setting where Frank has been resting and preparing to resume painting. His friend Jack Armitage is present, and they discuss art and philosophy, which sets the stage for Frank's internal struggles. The chapter details Frank's reflection on his past, his relationship with Margery, and the haunting memories that arise, symbolized by a crumpled concert program he discovers. As he begins to contemplate painting his self-portrait, he expresses fears surrounding the loss of his personal identity and the potential consequences of unveiling his true self through art. This complex interplay of emotions suggests that the portrait may not only reflect his physical likeness but also his darker, hidden aspects. (This is an automatically generated summary.)
Release date is 2014-06-23
Produced by Ema Majut and Marc D'Hooghe (Images generously made available by the Internet Archive.)
Keywords: Artists -- Fiction; Paranormal fiction; Repentance -- Fiction; Husband and wife -- Fiction